Advance in Research on Mycobacterium tuberculosis FabG4 and Its Inhibitor - Dutta, Debajyoti (Frontiers in Microbiology, 2018)
Increasing evidence from recent reports of drug-resistant mycobacterial strains poses a challenge worldwide. Drug-resistant strains often undergo mutations, adopt alternative pathways, and express drug efflux pumps to reduce or eliminate drug doses. Besides these intrinsic resistance mechanisms, bacteria can evade drug doses by forming biofilms. Biofilms are the concerted growth of adherent microorganisms, which can also be formed at the air-water interface. The growth is supported by the extracellular polymer matrix which is self-produced by the microorganisms. Reduced metabolic activity in a nutrient-deficient environment in the biofilm may cause the microorganisms to take alternative pathways that can make the microorganisms recalcitrant to the drug doses. Recent works have shown that Mycobacterium tuberculosis expresses several proteins during its growth in biofilm, those when deleted, did not show any effect on mycobacterial growth in normal nutrient-sufficient conditions. Studying these unconventional proteins in mycobacterial biofilms is therefore of utmost importance. In this article, I will discuss one such mycobacterial biofilm-related protein FabG4 that is recently shown to be important for mycobacterial survival in the presence of antibiotic stressors and limited nutrient condition. In an attempt to find more effective FabG4 inhibitors and its importance in biofilm forming M. tuberculosis, present knowledge about FabG4 and its known inhibitors are discussed. Based on the existing data, a putative role of FabG4 is also suggested.